Jargons and the formation of gamer’s identity in VALORANT Champions Tour 2021 - Rizki Perdana Sucipto; Tito Dimas Atmawijaya (Universitas Pakuan, 2025)
This study investigates the forms and meanings of jargons used by casters during the VALORANT Champions Tour (VCT) 2021 Korea Grand Finals, focusing on how these specialized terms function within the esports speech community. Using a descriptive qualitative approach, the research analyzed three YouTube videos of the final match to identify and classify 39 jargon terms based on Yule’s (2020) theory of word formation. The findings revealed that the most dominant word formation process was compounding, accounting for 15 of the 39 terms, followed by borrowing, etymological adaptation, clipping, coinage, acronyms, and conversion. The meanings of these jargons were interpreted through semantic analysis and were supported by contextual usage and, where relevant, specialized gaming sources. The results demonstrate that jargon in the esports domain not only facilitates efficient communication among players, casters, and fans but also reinforces group identity and shared knowledge. This research highlights how language evolves in digital and competitive environments, emphasizing the creative and social functions of jargon in online gaming culture.